Eclapsia: Still a Major Cause for Adverse Maternal and Perinatal Outcome (Medical Forum Monthly, 2024)
Objective: To determine the frequency of eclampsia and to investigate the maternal and perinatal outcome of the condition in order to identify whether further improvements can be made to the care of women by early interventions.Study Design: A descriptive observational study.Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology, Ghulam Muhammad Mahar Medical College Teaching Hospital Khairpur Mir,s Sindh, during one year period from 1st January to 31st December 2010.Material and Methods: All patients presenting with eclampsia in the labour room were included in the study. The diagnosis was based on case definition and was managed according to the set protocols. Data was recorded on pre-designed Performa.Results: A total of 2796 patients were admitted in labour room during the study period and out of them total cases of eclampsia were 81 patients thus contributing 2.89% of the total admission. Most of the patients were unbooked only 11% patients were booked. 49% of women had first fit in the antenatal period, 37% in intrapartum while 13.5% had first fit in postpartum period. Headache and raised blood pressure was found in 85% of cases. 91% of women received magnesium sulphate , platelet count <150,000/m3 were found in9.8%, deranged LFT in 14.8% women and abnormal renal function test were found in 34% . Mode of delivery was caesarean section in 57% patients, vaginal delivery in 34.2%. Two patient needed hysterectomies due to severe PPH, 4 maternal deaths were observed in study population. Regarding perinatal outcome 35 fetuses born with LBW, 26 were still born and 9 died in neonatal period.Conclusion: Eclampsia has strongly significant adverse impact on mother and fetus, which could be avoided by provision of integrated, adequate MCH services especially during antenatal period.